Frequency of pathogenic germline variants in pediatric medulloblastoma survivors - Rees, Donald; Gianferante, D. Matthew; Kim, Jung; Stavrou, Theodora; Reaman, Gregory; Sapkota, Yadav; Gramatges, M. Monica; Morton, Lindsay M.; Hudson, Melissa M.; Armstrong, Gregory T.; Freedman, Neal D.; Huang, Wen-Yi; et al. (Frontiers in Oncology, 2024)
Background: Medulloblastoma is the most common malignant brain tumor in children. Most cases are sporadic, but well characterized germline alterations in APC, ELP1, GPR161, PTCH1, SUFU, and TP53 predispose to medulloblastoma. However, knowledge about pathogenic/likely pathogenic (P/LP) variants that predispose to medulloblastoma vary based on genes evaluated, patient demographics, and pathogenicity definitions.Methods: Germline exome sequencing was conducted on 160 childhood survivors of medulloblastoma. Analyses focused on rare variants in 239 known cancer susceptibility genes (CSGs). P/LP variants were identified using ClinVar and InterVar. Variants of unknown significance in known medulloblastoma predisposing genes (APC, ELP1, GPR161, PTCH1, SUFU, TP53) were further classified for loss of function variants. We compared the frequency of P/LP variants in cases to that in 1,259 cancer-free adult controls.Results: Twenty cases (12.5%) had a P/LP variant in an autosomal dominant CSG versus 5% in controls (p=1.0 x10 -3 ), and 10 (6.3%) of these were P/LP variants in a known medulloblastoma gene, significantly greater than 0.2% observed in controls (p=1.4x10 -8 ). The CSGs with the most P/LP variants in cases, and significantly higher than controls, were ELP1 (p=3.0x10 -4 ) and SUFU (p=1.4x10 -3 ).Approximately one in eight pediatric medulloblastoma survivors had an autosomal dominant P/LP CSG variant. We confirm several known associated genes and identify novel genes that may be important in medulloblastoma.